Teacher-Student’s Interaction Analyzes on Physics Learning through Lesson Analysis (Case Study: Lesson Study Implementation in SMA Pontianak) - Erwina Oktavianty; Reni Marlina; Hamdani Hamdani; Syaiful B Arsyid; Raga Patria (Universitas Lambung Mangkurat, 2022)
Through lesson analysis, this research analyzed teacher interaction in science classes, particularly in physics classes in one of the secondary schools at Pontianak, West Kalimantan. A qualitative method is used in this study by analyzing tape recording and video. This study has four stages of implementing lesson study cycles. It starts with planning lesson design, implementation with observation containing student and teacher responses during the lesson, reflection, and revised lesson design. Video tapped, and transcripts are employed in each lesson. The analysis showed that a teacher dominated the lesson at 62.3%, while students only made up 37.4% of the total conversations during their lessons. Knowing the interaction of teacher and students in the learning process could help the teacher to make improvements in learning based on reflections from the responses of students and teachers.